20-years cumulative impact from shrimp farming on mangroves of northeast Brazil - Lacerda, Luiz Drude de (2021)
Brazilian mangroves cover about 11,100 km2 and provide a wide range of ecosystem services. Despite their importance, they are one of the most impacted ecosystems because of combined influences of climate change, pollution, and direct conversion and loss. A major driver of environmental impacts is shrimp farming and this is particularly acute in the semi-arid northeast of Brazil, where mangroves are constrained in a narrow band along ephemeral estuaries that are often impacted by multi-year droughts. Recent changes to Brazilian law, in particular the Forest Code, have weakened protection for mangroves and associated “apicum” (salt pan) ecosystems. In NE Brazil, most shrimp ponds are converted from mangrove-adjacent “apicuns” rather than the mangroves themselves with periodic hydrological connectivity through dammed channels, allowing the flushing of effluents. As a result, the main impacts on mangroves are typically indirect, because of pollution inputs from shrimp pond effluents and associated loss of ecosystem services including reductions in primary productivity, carbon storage capacity, resilience to other environmental stressors, their efficiency as estuarine filters, and biodiversity and abundance of subsistence use of marine species. Soil damage and infrastructure remaining after shrimp pond deactivation impairs mangrove recovery. This extends the duration of the damage and allows the occupation of degraded areas by other activities that can permanently impair ecosystem function. In this review, we address several aspects of the shrimp culture boom in NE Brazilian, their features and consequences, and the future of mangroves in the region considering climate change and rising poverty. Our conclusions on the practices and outcomes of shrimp farming in mangroves are likely to apply to areas with similar environmental settings, e.g., semiarid regions worldwide, and particularly in the Latin America and Caribbean region, and our findings can be taken into account to improve conservation and management of these forests at the least to a regional scale.